Communication and well-being outcomes of a hybrid service delivery model of intensive impairment-based treatment for aphasia in the hospital setting: a pilot study. Issue 13 (19th June 2018) - Wenke, Rachel; Cardell, Elizabeth; Lawrie, Melissa; Gunning, Dana
Abstract: Purpose: This pilot study aimed to evaluate the effects of an intensive hybrid service delivery model (i.e., combining face-to-face individual, computer and group therapy) on communication and well-being for people with aphasia (PWA) in the hospital setting. Materials and methods: The study explored two different intensities of the hybrid model, 4 h/week (Hybrid-4) and 8 h/week (Hybrid-8) both for 8 weeks. Participants ranging from 1 month to 5 years post-onset were allocated using matched-pair randomisation to receive either Hybrid-4 ( n  = 5) or Hybrid-8 ( n  = 4) and assessed using a comprehensive language battery by a blinded assessor, as well as selected activity, participation and well-being measures before, immediately after and 4-week post-treatment. Results: All participants in Hybrid-4 and three out of four participants in Hybrid-8 demonstrated clinically significant improvement to measures of language impairment immediately post-treatment, with the majority also demonstrating maintenance effects 4-week post-treatment. Clinically significant improvements to activity, participation and well-being measures were also observed across participants in both groups. Conclusions: Findings support the potential benefit of employing an intensive hybrid service model and suggest that both 4 and 8 h per week of impairment-based treatment for 8 weeks may result in improvements in communication and well-being for some PWA across different stages of recovery. Implications for rehabilitation: The present findings help bridge the gap between what evidence suggests is effective intensity of rehabilitation for aphasia and what can be practically delivered in real-world hospital settings. Findings support the potential clinical value of employing a hybrid service model (using computer, group and individual therapy) to deliver intensive rehabilitation to people with aphasia in the hospital setting, and suggest that clinically significant improvements to communication and well-being can result when the model is delivered at either 4 or 8 h per week. The current study highlights that people with aphasia in the early stages of aphasia recovery can potentially benefit from intensive impairment-based hybrid models of intervention.